Performance of RESIST-3 OKN K-SeT immunochromatographic assay for the detection of OXA-48 like, KPC, and NDM carbapenemases in Klebsiella pneumoniae in Turkey - ALTINKANAT GELMEZ, GÜLŞEN; HASDEMİR GÖKBOĞA, MÜNEVVER UFUK (SPRINGER, 2018)
In this study, the performance of the RESIST-3 O.K.N. K-SeT (Cofis BioConcept, Gembloux, Belgium) immunochromatographic assay was evaluated in 132 Klebsiella pneumoniae comprising 102 carbapenem resistant and 30 carbapenem susceptible isolates. Genotypically known isolates of Gram negative bacteria (n = 22) including various species were also tested by the assay as controls. The isolates tested by the immunochromatographic assay and also were run PCR for bla(KPC), bla(VIM) bla(NDM), and bla(OXA-48). The rates of bla(NDM), bla(OXA-48), and bla(KPC) in carbapenem resistant isolates were found at 52.9%, 39.2%, and 2.0%, respectively. Both bla(NDM) and bla(OXA-48) were found in six (5.9%) isolates. The results of the assay showed 100% concordance with those obtained by PCR in 132 K. pneumoniae. The agreement between the two methods was found to be identical at the isolate level. The assay also correctly detected all genotypically known isolates of Escherichia coli, Serratia marcescens, Citrobacter freundii, Enterobacter cloacae, K. pneumoniae carrying bla(KPC), bla(NDM), and/or bla(OXA-48). On the other hand, the assay did not exhibit any cross-reaction in control isolates harboring bla(IMP) and bla(VIM). We conclude that the RESIST-3 O.K.N. K-SeT is a reliable, rapid, and user friendly test and we recommend it for routine diagnostic laboratories. (C) 2018 Sociedade Brasileira de Microbiologia. Published by Elsevier Editora Ltda.
Keywords: Klebsiella pneumoniae; Immunochromatographic test; NDM; KPC; OXA-48; RAPID DETECTION; ESCHERICHIA-COLI; PSEUDOMONAS-AERUGINOSA; 1ST REPORT; ENTEROBACTERIACEAE; IDENTIFICATION; ISTANBUL; STRAINS; OXA-181; ISOLATE